GENERATING MULTIPLE TIME SERIES FORECASTS WITH ARTIFICIAL NEURAL NETWORKS IN A TELECOMMUNICATIONS COMPANY - Cabrera-Rios, Mauricio (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
<!–StartFragment–> In this work, the generation of multiple period demand forecasts was approached through the use of artificial neural networks (ANNs) for time series. The study was carried out for a telecommunications company and called for the use of a method to fine-tune the ANNs by using design of experiments (DOE) and optimization techniques. The results give evidence of better forecasting performance of the ANNs over traditional statistical techniques. <!–EndFragment–>